2021
DOI: 10.3390/s21217113
|View full text |Cite
|
Sign up to set email alerts
|

Weather Sensing in an Urban Environment with the Use of a UAV and WebRTC-Based Platform: A Pilot Study

Abstract: Thanks to IoT, Internet access, and low-cost sensors, it has become possible to increase the number of weather measuring points; hence, the density of the deployment of sources that provide weather data for the needs of large recipients, for example, weather web services or smart city management systems, has also increased. This paper presents a flying weather station that carries out measurements of two weather factors that are typically included in weather stations (ambient temperature and relative humidity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Furthermore, implementing this model helps to integrate with a complete processing algorithm to achieve efficient samples from input images and minimize hyperparameter tuning indicators. It achieves the same performance improvements while avoiding complexity by optimizing the basics of the Clipped Surrogate Objective (7).…”
Section: ) Ppo-based Tf-agentmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, implementing this model helps to integrate with a complete processing algorithm to achieve efficient samples from input images and minimize hyperparameter tuning indicators. It achieves the same performance improvements while avoiding complexity by optimizing the basics of the Clipped Surrogate Objective (7).…”
Section: ) Ppo-based Tf-agentmentioning
confidence: 89%
“…In most cases, it can be beneficial for increasing the productivity of large plantations with congenerous growers to determine drainage patterns and wetdry spots of field elevation that allow more efficient watering techniques. Moreover, there are several fields in which drones are being applied, such as surveillance and controlling large unreachable areas [3], drones for medical purposes such as Automated Emergency Drones (AED) [4], and autonomous drones for search and rescue operations [5], in UAV-based road traffic monitoring applications [6], drones for weather sensing in an urban environment application [7], emergency drone system applications for firefighter processes [8], and drones for entertainment: photography and cinematography [9]. Many recent innovations and technologies related to UAV frameworks include surveillance and target tracking units for several reasons, including security maintenance, control, military assistance, and traffic monitoring, besides manufacturing optimization and control.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical research focus is on the development of sophisticated data assimilation and modeling techniques [13,[28][29][30]. Integrating data collected from UAVs into meteorological models is essential for enhancing the accuracy of weather forecasts and climate models.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The unmanned aerial vehicle (UAV) and Web Real-Time Communications (WebRTC)based platform for monitoring urban and industrial areas, reported in our previous paper [29], combines IoT-based measurements with video from 4K camera and WebRTC [30][31][32], which was fully standardized this year [31,33] using the technology of native real-time transmission between Web browsers. One of the proposed new use cases of the WebRTC is the IoT [34] and, more precisely, the Web of Things (WoT), i.e., the integration of smart things with the Web [35].…”
Section: Uav and Webrtc-based Platform For Monitoring Urban And Indus...mentioning
confidence: 99%
“…The experience gained during the design and implementation of the early prototype of the WebRTC-based flying monitoring system [36] was used during the construction of the UAV and WebRTC-based framework [37]. This framework was the basis of the mobile weather monitoring system [29]. This paper is focused on another purpose for the framework, which is the Kestrel, i.e., the system intended for widely understood environmental measurements carried out by air.…”
Section: Main Contributions and Organization Of This Papermentioning
confidence: 99%